Myasthenia gravis as a presenting feature in a patient with lung cancer: A case report - Vahid Shaygannejad (Journal of Research in Medical Sciences, 2011)
A male patient with muscle weakness had clinical findings of ptosis, diplopia, proximal leg weakness, and positive repetitive nerve stimulation (RNS) test. He demonstrated positive acetylcholine receptor antibody. This lung cancer patient was presenting myasthenia gravis. The causal association between non-small-cell lung cancer and non-thymomatous myasthenia gravis has not been clarified yet. To date, there has been no evidence supporting the speculation that association of myasthenia gravis with lung cancer might be one of the phenotypes of paraneoplastic syndrome.